Stable isotope and chemical inhibition analyses suggested the existence of a non-mevalonate-like pathway in the yeast Yarrowia lipolytica - Dissook, Sivamoke (Sci Rep, 2021)
Methyl erythritol phosphate (MEP) is the metabolite found in the MEP pathway for isoprenoid biosynthesis, which is known to be utilized by plants, algae, and bacteria. In this study, an unprecedented observation was found in the oleaginous yeast Yarrowia lipolytica, in which one of the chromatographic peaks was annotated as MEP when cultivated in the nitrogen limiting condition. This finding raised an interesting hypothesis of whether Y. lipolytica utilizes the MEP pathway for isoprenoid biosynthesis or not, because there is no report of yeast harboring the MEP pathway. Three independent approaches were used to investigate the existence of the MEP pathway in Y. lipolytica; the spiking of the authentic standard, the MEP pathway inhibitor, and the (13)C labeling incorporation analysis. The study suggested that the mevalonate and MEP pathways co-exist in Y. lipolytica and the nitrogen limiting condition triggers the utilization of the MEP pathway in Y. lipolytica.